Prevalence of anxiety and depression among doctors; the unscreened and undiagnosed clientele in Lahore, Pakistan - Atif, Khaula (Pak J Med Sci, 2016)
OBJECTIVES: To analyze prevalence of anxiety and depression among doctors serving in a tertiary care hospital in Lahore, with a study of impact of relevant demographic features. METHODS: A cross sectional study was conducted at Combined Military Hospital, Lahore, from February 2014 to Jan 2015. Participants were doctors serving in subject hospital for at least six months duration. Standardized Hospital Anxiety Depression Score (HADS) inventory was selected as inventory. Formal approval from hospital ethical committee and written informed consent from participants were obtained. Demographic characteristics of participants were recorded as independent variables; anxiety and depression scores being outcome variables. Data analysis was done via descriptive statistics (SPSS-20), qualitative data expressed as frequencies, percentages; quantitative as mean ± standard deviation(SD). Cross tabulation was done via chi-square, p-value < 0.05 considered as significant. RESULTS: Out of 203 volunteers, 97(47.78%) responded. Score of anxiety was 7.04±4.470, maximum being 19, scores of depression was 4.94±3.605, maximum score being 15. Mild to moderate anxiety and depression were revealed in 33(34%) and 24(24.8%) respectively, while 7(7.2%) and 1(1.0%) had severe anxiety and depression respectively. There was strong positive relation between anxiety and depression (p<0.001). There was significant impact of service years on depression (p-0.011) and gender on anxiety (p-0.002), 9(17.31%) males and 24(53.33%) females had mild to moderate anxiety while 4(7.69%) males and 3(6.66%) females revealed severe anxiety and other variables did not reveal significant impact on HADS scores. CONCLUSION: Doctors showed high grades of anxiety and depression. They must be promptly screened and managed at all medical institutions.